Shorting Resection and Correction of the Leg Length in the Treatment of Posttramatic Tibial Defects Complicated by Osteomyelitis - A. A. Artemiev; P. A. Ivanov; A. M. Kashoob; M. A. Grigoriev; R. A. Gandzhaliev; Yu. S. Soloviev; I. A. Sysoev (Неотложная медицинская помощь)
Background. Severe fractures of the shin bones are often accompanied by the formation of defects in the tibia, suppuration and soft tissue necrosis. In the case of surgical treatment of fractures, infectious complications reach 3.6-9.1%. One of the methods of treatment of infected defects is resection of the ends of the tibia with shortening. This operation has proven to be effective in the treatment of fresh fractures. The relevance of the work is due to the prospects of using this technique in the treatment of the consequences of fractures with the formation of infected defects of the tibia.Aim of the study. Improving the results of treatment of patients with post-traumatic defects of the tibia complicated by osteomyelitis by performing a shortening resection with simultaneous or sequential correction of the segment length.Material and methods. The results of treatment of 65 patients with diaphyseal post-traumatic tibial defects complicated by osteomyelitis were analysed. They were divided into 2 groups. Group 1 was formed by 31 (47.7%) patients, they underwent shortening resection of the ends of bone fragments in the defect zone with simultaneous lengthening at another level. Group 2 included 34 (52.3%) patients who underwent a shortening resection of the tibia without lengthening. In all cases, the Ilizarov apparatus was used as a fixator.Results. The technique for assessing the size of the true defect of the tibia was optimized taking into account the initial shortening of the segment and the distance between the proximal and distal fragments after resection of their ends. A treatment regimen was developed depending on the level of localization of the tibial defect, and the results of treatment of patients in the compared groups were assessed.Conclusion. Shortening resection is an effective treatment for patients with post-traumatic tibial defects complicated by osteomyelitis. Depending on the level of localization of the defect, it is advisable to carry out treatment according to one of two possible options. When the defect is localized in the upper and middle third of the tibia, shortening resection in an isolated form is shown. If the defect is localized in the lower third of the tibia, it is possible to supplement the shortening resection with an osteotomy in the upper third with Ilizarov lengthening.